Pengendalian Gulma Paku di Areal Gambut Menggunakan Beberapa Jenis Bahan Aktif Herbisida - Kartirahayu Kusumaningsih; Setiaji Heri Saputra; Muhardi (Jurnal Wana Tropika, 2022)
Fern weeds control with chemical herbicide in peat area is one solution to overcome weeds competition against cultivated plants at timber estate. Type of active component and solution concentrate of herbicide are effect on weed control result. The purpose of this research are to know weed species and its density, and effect of  active component type and solution concentration of herbicide against weed mortality percentage and weed mortality start time. Results of the research showed that Stenochlaena palustris weed was dominated at peat area with 3.986/Ha density. Ammonium Glufosinat herbicide with 1,6% solution concentration was effective to control fern weeds with 100% weed mortality and start time of weed mortality was 3 days after herbicide application.